Plastic waste management using a Life Cycle Assessment (LCA) approach: A step toward improving sustainability literacy - Siti Fatimah; Margareta Rahayuningsih; Aditya Marianti; Alfred Irambona (Universitas Sebelas Maret, 2024)
Plastic waste has become a serious issue for the environment and health. This study aims to analyze the management of plastic waste using the LCA approach and its influence on sustainability literacy in science learning. The research utilizes a mixed-methods exploratory sequential design. It begins with qualitative data collection through observation, interviews, and documentation, followed by quantitative data collection through experimental design. Sustainability literacy is assessed using a Sustainability Literacy questionnaire. Data analysis techniques include data condensation, data display, and data verification. Hypothesis testing is conducted using t-tests. The analysis results suggest that the LCA approach can be an alternative to managing plastic waste. LCA provides a systematic process consisting of goal formulation, data inventory, impact assessment, and interpretation. Knowledge and understanding of plastic waste management are efforts to promote sustainability literacy among university students. The sustainability literacy profile of students is categorized as very good. In terms of t-test analysis results, the SSIBL model proves to influence students' sustainability literacy with a significance value of 0.042.